Primary malignant melanoma of breast: A unique case report - Patel, Rajas B; Dhabhar, Boman N; Behl, Arun (Indian Journal of Case Reports, 2019)
Malignant melanoma is a clinical entity that occurs commonly in the skin, mucous membrane, and choroid; its occurrence in breast tissue is extremely rare. Evidence suggests that most malignant melanoma cases present as a metastatic manifestation of primary cutaneous melanoma. It is rare to find primary malignant melanoma of breast tissue. There is a dearth of data on this topic in the academic literature; moreover, there are no standard guidelines or consensus statements available on the management of primary malignant melanoma of the breast. Therefore, we, herein, report one such rare case of malignant melanoma with breast as its primary site.